"Because She Knew That I Did Not Have a Social": Ad Hoc Guidance Strategies for Latino Undocumented Students. (January 2017) - Lauby, Fanny
Understanding the challenges of Latino undocumented students in high school is crucial to improving their success rates in college. Based on interviews with 60 Latino undocumented youths, I explore the barriers to proper educational guidance for this population. Results indicate that undocumented youths often lack accurate information about college, and that schools can provide negative contexts of bureaucratic incorporation. As a result, undocumented youths devise their own ad hoc strategies for gaining access to college.